2012
DOI: 10.1155/2012/427407
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Medical and Psychobehavioral Emergency Department Visits Made by Adults with Intellectual Disabilities

Abstract: Study Objective. We describe and contrast medical to psychobehavioral emergency visits made by a cohort of adults with intellectual disabilities. Methods. This was a study of 221 patients with intellectual disabilities who visited the emergency department because of a psychobehavioral or medical emergency. Patient profiles are described and logistic regression was used to assess predictors of psychobehavioral emergencies in this group, including age, residence, psychiatric diagnosis, cognitive level, and life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to examine the reasons for hospital ED consultation specifically among persons with PID and to show that in most cases, this is due to somatic problems. This finding is consistent with some previous studies of the broad population of people with ID (McDonald 1985;Whitaker & Read 2006;Findlay et al 2014), although other reports have suggested that psychiatric problems account for a greater proportion of hospital consultations and admissions among people with ID (Balogh et al 2005;Lunsky & Balogh 2010;Lunsky et al 2012c;Tint & Lunsky 2015). In this respect, it is worth noting that in our study group, there were no ED consultations due to attempted suicide or, apparently, to stressful life events, these being circumstances that appear to become more common as intellectual ability increases (Lunsky & Elserafi 2011b;Lunsky et al 2012d).…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first study to examine the reasons for hospital ED consultation specifically among persons with PID and to show that in most cases, this is due to somatic problems. This finding is consistent with some previous studies of the broad population of people with ID (McDonald 1985;Whitaker & Read 2006;Findlay et al 2014), although other reports have suggested that psychiatric problems account for a greater proportion of hospital consultations and admissions among people with ID (Balogh et al 2005;Lunsky & Balogh 2010;Lunsky et al 2012c;Tint & Lunsky 2015). In this respect, it is worth noting that in our study group, there were no ED consultations due to attempted suicide or, apparently, to stressful life events, these being circumstances that appear to become more common as intellectual ability increases (Lunsky & Elserafi 2011b;Lunsky et al 2012d).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous research on ED use in individuals with intellectual disabilities who may not have ASD, we found the most common medical presentation was injury, and one of the most common mental health presentations was aggression 20. There were situations where emotional distress led to the medical emergency and instances where an unaddressed medical concern presented as self-injury or aggression.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to the methodology adopted in a previous paper,20 ED descriptions were classified by two independent coders (MP-S, YL) as being caused by a medical or mental health issue; where there were discrepancies, the case was discussed until consensus was reached. The majority of the emergencies were classified as medical in nature (65.4%), with injury accounting for 58.8% of medical ED visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Families with children affected by ID and/or ASDs may have particular difficulty in accessing primary and specialist healthcare services, leading to emergency department presentations and hospitalisation rates greater than those not affected by these disorders. A further Canadian study 20 found that admissions to an emergency department for people with ID were more likely to be for a psychobehavioural rather than a medical reason. However, there are less population-based data describing the pattern of hospitalisation among children with ID or ASD.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%